The Optimisation of the Initial Phase of The Project Process, with a focus on information, communication & requirement management - PEKTAS, AYLIN (My University, 2016)
The initial phase is the first phase of the project life cycle and it plays an important role since it deals with vast amount of information and documentation, which becomes the evidence of the project. The initial phase has a great impact on the effectiveness of the project progress and the success of the project outcome. Inefficient and ineffective management of these three areas results in a high risk of project time delays and project over costs. Therefore it is the benefit to all stakeholders for the management of the initial phase to be as efficient and effective as possible. This study looks into how the initial phase of the project process can be optimised through information, communication and requirement management. Furthermore this study investigates if there could be a defined structure to be applied in every project in order to achieve effectiveness. This study also looks into what challenges are faced in the Swedish construction market related to information, communication and requirement management. Furthermore, the matter is approached with a broad perspective and should be seen as a foundation and guidance for future detail studies. In addition, all relevant life cycle phases are overviewed with the belief that efficiency in the initial phase is achieved when it is consistent throughout the project life cycle. The result of this study is based on 6 detailed interviews conducted with representative employees in a consultancy company. These employees are in various positions related to construction. By discussing the results with the comprehensive theoretical framework of this study, this study finds that the management of information, communication and requirements are dependent on various factors. The most dominant two factors are the client and the project manager. This study shows that the optimisation of the initial phase is possible by developing frameworks for the different conditions that the client and the project manager create. The idea of a defined structure to be used in every project is discussed and supported by various authors. The challenges faced in the Swedish construction market are identified and it is recommended to take these into consideration to gain quick and beneficial results in the company. It also recommended to study project delivery systems (design build and design bid build) and to develop management structures accordingly. Furthermore using the wide approach that this study presents of the matter to develop structures for optimisation is recommended.
Keywords: Samhällsbyggnadsteknik; Civil Engineering